Eyelid Tumours: An Institutional Experience on Clinicopathological Profile and Management - BR, Kiran Kumar; S, Arpitha; Narayanan, Geeta S (Asian Pacific Journal of Cancer Biology, 2024)
Background: Primary cancer of the eyelid is an uncom¬mon malignancy with a metastatic potential. The objective of this study to assess the clinicopathological profile, management management strategies and build awareness about the more aggressive eyelid malignancies to reduce morbidity and mortality. Methods: Retrospective analysis of all the eyelid tumours presented to our institute from 2015 to 2021 was done. A total of 10 patients with histopathologically proven malignant eyelid tumours of all age groups were included in the study. All information regarding clinical details, treatment and outcomes were retrospectively collected and analysed. Results: The most common malignant eyelid tumour was basal cell carcinoma (n=5) followed by squamous cell carcinoma (n=3), Malignant Melanoma (n=1) and sebaceous gland carcinoma (n=1). Mean age of all patients with malignant eyelid tumour at the time of diagnosis was 61 years. Females were more frequently affected than males. The proportion of involvement of lower eyelid was significantly higher than of upper eyelid in basal cell carcinoma (P = 0.045). All patients were managed by surgical excision with tumour-free margins verified on histopathology followed by eyelid reconstruction and adjuvant radiotherapy was given in patients meeting high risk criteria. Conclusions: Basal cell carcinoma was the most common eyelid malignancy observed and is more frequent in women than in men. Surgery is the mainstay of treatment and adjuvant radiation in high-risk patients provides excellent locoregional control.